Pemikiran Filsafat Pendidikan Ikhwanu Sh-Shafa dan Ibnu Miskawaih - Feri Firmansyah; Rafa Riansyah; Muhammad Revashah Al-Ghani; Wildan Nasrun Hakim; , Muhamad Parhan (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study aims to analyze the philosophical thoughts of Ikhwān al-Ṣafā and Ibn Miskawaih and their relevance to contemporary Islamic education. Using a qualitative approach with literature study methods, this research explores the epistemological, ethical, and educational methodologies of both figures. The findings indicate that the collective-encyclopedic epistemology of Ikhwān al-Ṣafā and the systematic-individual approach of Ibn Miskawaih both emphasize the integration of knowledge with Islamic ethical values. The concept of al-wasath (the middle path) in Ibn Miskawaih’s ethics and the intellectual freedom promoted by Ikhwān al-Ṣafā provide a strong philosophical foundation for character education in the digital era. The synthesis of their ideas results in a holistic Islamic educational framework that addresses the dichotomy of knowledge and the moral crisis in modern education.